Effect of near-wall blockage on the magnetohydrodynamics-based double-diffusive convection in rectangular cavities - Kumar, Sudhanshu; Gangawane, Krunal M.; Öztop, Hakan Fehmi; Panda, Sibasish (Taylor & Francis Inc, 2025)
This research work reports the numerical investigation of magnetohydrodynamics (MHD) characteristics around the near-wall blockage (NWB) for various separation distances owing to double-diffusive convection (DDC) in a rectangular cavity. The distance between the bottom wall of the cavity and the lower wall of blockage is called separation distance Sd, and it has varied from (H/4 <= Sd <= H/8), where H is the height of the cavity. The working fluid is considered as liquid metal - Sodium-Potassium alloy (Pr=0.054). The numerical computations are conducted by using an in-house developed lattice Boltzmann method (LBM) solver. The simulations are conducted for the steady-state, laminar, incompressible, and Newtonian fluid flow. The effect of NWB has been explored for a range of parameters, such as Rayleigh number (Ra=104 and 105), Lewis number (0.5 <= Le <= 1.5), buoyancy ratio (-1.5 <= N <= 1) and Hartmann number (0 <= Ha <= 300). The variation and contour plots show the higher heat and mass transfer (HMT) rates for Sd=H/4 at constant Ra. As Sd increases, HMT rates enhance. The increase in Ra, N, and Le induces multiple-cell formation inside the cavity for a given Sd. As Ha augments HMT rates get decreased monotonically. For Ha >= 150, negligible or slight variation was observed in the rate of HMT. As the obstruction between the bottom wall of the blockage and the adiabatic bottom wall of the cavity increases, shear force occurs, and the buoyancy-driven flow decreases. The outcomes of the numerical investigation are summarized in the form of empirical correlation of NuTotal for Ra = 104 and 105 at various separation distances, which might be utilized for probable design purposes.
Keywords: Double-diffusive convection; lattice Boltzmann method; magnetohydrodynamics; near-wall blockage; separation distance